Transformasi Perilaku Konsumen Akibat Adopsi Teknologi Digital Studi tentang Penggunaan E-Commerce dan Pembayaran Non-Tunai - Andry Irdyansah; Harini Harini; Nila Masalikul Masruroh (Universitas Ivet, 2025)
This study aims to deeply analyze the transformation of consumer behavior triggered by the adoption of digital technology, specifically in the context of e-commerce utilization and non-cash payment. The digital era has reshaped the traditional buying cycle into a faster, more efficient, and personalized process. The research method employed is a systematic literature review of relevant studies within the last five years, supported by secondary data on the growth of digital transactions. The findings reveal a significant shift from conventional rational buying behavior towards behavior driven by convenience, information accessibility, and the personalized customer experience offered by digital platforms. The adoption of e-commerce and non-cash payment (such as mobile banking and e-wallets) not only affects the purchase stage but also alters the information search stage (dominated by online reviews) and the post-purchase evaluation (via ratings and feedback). The implication of this transformation requires businesses to implement omnichannel strategies and prioritize consumer data security to maintain loyalty in an increasingly competitive market.